Coupling of 3D Bio-printing with Organ-on-a-chip Technology Creates New Possibility for Biomimicry - Luo, Yong (Journal of 3D Printing and Applications, 2018)
Editorial reflects on pairing 3D bioprinting with organ-on-a-chip systems to build tissue models that feel closer to living organs. The author discusses how microfluidic chips can nourish printed constructs, acknowledges scale hurdles, and invites researchers to share practical experiments in drug testing and regenerative medicine.
Keywords: 3D Bioprinting; Organ-on-a-chip; Drug Testing; Regenerative Medicine; Biomimicry